2015
DOI: 10.1177/1934578x1501000622
|View full text |Cite
|
Sign up to set email alerts
|

Structure Revision of Two Polyoxygenated Sterols from the Marine Sponge Neofibularia nolitangere

Abstract: Careful reexamination of the published 1 Hand 13 C-NMR spectral data of (24S)-24-ethylcholest-8-ene-3,5,6,7-tetraol (1) and (24S)-24-ethylcholest-8(14)-ene-3,5,6,7-tetraol (2), isolated from the marine sponge Neofibularia nolitangere, indicates that, in reality, compounds 1 and 2 are (24S)-5,6epoxy-24-ethylcholest-8-ene-3,7-diol (9) and (24S)-5,6-epoxy-24-ethylcholest-8(14)-ene-3,7-diol (10), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Sterols having a 3,5,6,7-tetrahydroxylated structure did not show a molecular ion in the EIMS and showed the dehydration ion due to the loss of one molecule of H 2 O. However, the dehydration ion of sterols having a 3,5,6,7-tetrahydroxylated structure correspond to the molecular ion for sterols having a 3,7dihydroxy-5,6-epoxy structure [2]. The interpretation of the above EIMS data was responsible for the misassignment of the structure of sterols having a 3,5,6,7-tetrahydroxylated structure [2].…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Sterols having a 3,5,6,7-tetrahydroxylated structure did not show a molecular ion in the EIMS and showed the dehydration ion due to the loss of one molecule of H 2 O. However, the dehydration ion of sterols having a 3,5,6,7-tetrahydroxylated structure correspond to the molecular ion for sterols having a 3,7dihydroxy-5,6-epoxy structure [2]. The interpretation of the above EIMS data was responsible for the misassignment of the structure of sterols having a 3,5,6,7-tetrahydroxylated structure [2].…”
mentioning
confidence: 91%
“…The novel 3,5,6,7tetrahydroxylated structure of 1 was proposed on the basis of 1D and 2D NMR spectral data [1]. Recently we reported the structure revision of a sterol having the same A/B ring system as that of 1, (24S)-24-ethylcholest-8(14)-ene-3,5,6,7-tetraol (2), from the marine sponge Neofibularia nolitangere ( Figure 1) [2]. The structure of 2 was revised to 5,6-epoxy-(24S)-24-ethylcholest-8(14)-ene-3,7-diol (3) by reexamination of the published NMR data ( Figure 1) [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we reported the structure revision of two polyoxygenated sterols, (24S)-24-ethylcholest-8-ene-3,5,6,7-tetraol and (24S)-24-ethylcholest-8(14)-ene-3,5,6,7-tetraol, from the marine sponge Neofibularia nolitangere [1]. A thorough investigation of the literature data of the polyoxygenated sterols from natural sources revealed that the structure of (22E)-ergosta-7,22-diene-3,5,6,9,14-pentol (1), isolated from the spores of the medicinal mushroom Ganoderma lucidum, would need to be revised ( Figure 1) [2].…”
mentioning
confidence: 99%